Halophila stipulacea descriptors in the native area (Red Sea): A baseline for future comparisons with native and non-native populations. (January 2020) - Beca-Carretero, Pedro; Rotini, Alice; Mejia, Astrid; Migliore, Luciana; Vizzini, Salvatrice; Winters, Gidon
Abstract: Halophila stipulacea is a small tropical seagrass species native to the Red Sea. Due to its invasive character, there is growing interest in understanding its ability to thrive in a broad range of ecological niches. We studied temporal (February 2014 and July 2014), depth (5, 9, 18 m) and spatial (NB and SB) related dynamics of H. stipulacea meadows in the northern Gulf of Aqaba. We evaluated changes in density, morphometry, biomass, and biochemical parameters alongside the reproductive effort. In both sites, maximal growth and vegetative performance occurred in the summer with a marked increase of 35% in shoot density and 18% in biomass; PAR reduction with season and depth induced a significant increase of 28% in leaf area. Sexual reproduction efforts were only observed in July, and the density of plants carrying male or female flowers decreased significantly with depth. The favorable growth responses of H. stipulacea plants observed in the N-enriched NB site suggests their capacity to acclimate to human-disturbed nearshore environments. Highlights: H. stipulacea displayed contrasted responses to different environmental conditions. Higher phenol contents were observed in SB than in NB in both seasons. H. stipulacea plants positively acclimate to N-enriched marine systems. Most detailed quantitative baseline data of native Halophila stipulacea populations.